Analysis Level of Comfort, Safety and Safety Level on Pathways in The Kebayoran Baru Area, South Jakarta - Widyaningsih, Nunung; Adawiya, Aisha (Universitas Ibn Khaldun Bogor, 2023)
As the population increases, resulting in high human mobility. However, high mobility is not matched by services for transportation facilities and infrastructure, especially sidewalks. One of the areas with existing sidewalk problems is the Kebayoran Baru area of South Jakarta. The problem that occurs is that the sidewalk is used as a place to street vendors, and is used as an illegal parking lot. The methodology of this research was carried out by conducting a geometric survey, measuring the volume and travel time of pedestrians to determine the level of service and distributing questionnaires as 80 respondents to pedestrians in search of the level of performance and importance of sidewalk facilities. This data processing uses Microsoft Excel and Statistical Product and Service Solutions (SPSS). The results of the analysis carried out that the sidewalks do not meet the minimum standards according to regulations. From the measurement of the results of the volume and travel time of pedestrians, the level of service with category A is obtained, as well as the results of the questionnaire related to the level of comfort, security, and safety of pedestrians influenced by the presence of street vendors and illegal parking on sidewalks.